Regulation of Rfa2 phosphorylation in response to genotoxic stress in Candida albicans. Issue 1 (21st August 2014) - Gao, Jiaxin; Wang, Haitao; Wong, Ada Hang‐Heng; Zeng, Guisheng; Huang, Zhenxing; Wang, Yanming; Sang, Jianli; Wang, Yue
Summary Successful pathogens must be able to swiftly respond to and repair DNA damages inflicted by the host defence. The replication protein A (RPA) complex plays multiple roles in DNA damage response and is regulated by phosphorylation. However, the regulators of RPA phosphorylation remain unclear. Here, we investigated Rfa2 phosphorylation in the pathogenic fungus Candida albicans. Rfa2, a RFA subunit, is phosphorylated when DNA replication is inhibited by hydroxyurea and dephosphorylated during the recovery. By screening a phosphatase mutant library, we found that Pph3 associates with different regulatory subunits to differentially control Rfa2 dephosphorylation in stressed and unstressed cells. Site‐directed mutagenesis revealed T11, S18, S29, and S30 being critical for Rfa2 phosphorylation in response to genotoxic insult. We obtained evidence that the genome integrity checkpoint kinase Mec1 and the cyclin‐dependent kinase Clb2–Cdc28 mediate Rfa2 phosphorylation. Although cells expressing either a phosphomimetic or a non‐phosphorylatable version of Rfa2 had defects, the latter exhibited greater sensitivity to genotoxic challenge, failure to repair DNA damages and to deactivate Rad53‐mediated checkpoint pathways in a dosage‐dependent manner. These mutants were also less virulent in mice. Our results provide important new insights into the regulatory mechanism and biological significance of Rfa2 phosphorylation in C. albicans.